Influence of Instagram Exposure on People Happiness and Self Esteem - Siddiqa, Ayesha; Seçim, Gürcan; Mukhtar, Hafsa (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigated at how young people's perceptions of their self esteem and level of happiness in Northern Cyprus were affected by using Instagram. A quantitative study was conducted. 99% of the international students at Cyprus University who were between the ages of 18 and 30 contributed to the sample size of 380, which was determined using the Cochran formula. Data were gathered via an online questionnaire that included validated performance indicators such the Subjective Happiness Scale, the Instagram Intensity Scale, and the Rosenberg Self-Esteem Scale. The aim of the survey was to determine the participants' level of satisfaction and self-esteem while use Instagram. The study's findings indicated that young people's use of Instagram had a detrimental effect on their level of happiness. However, using Instagram positively impacted the self-esteem of those who idealised the selected portrayals of others on social media and engaged in upward social comparison. The study produced several helpful recommendations, such as helping kids develop their critical thinking and media literacy skills so they can evaluate and understand how social media affects their overall welfare and mental health. Provide mental health resources and support services to students who may be experiencing negative consequences on their mental health as a result of consuming social media.